Cyanobacteria-Derived Proline Increases Stress Tolerance in Arabidopsis thaliana Root Hairs by Suppressing Programmed Cell Death - Chua, Alysha; Sherwood, Orla L.; Fitzhenry, Laurence; Ng, Carl K.-Y.; McCabe, Paul F.; Daly, Cara T. (Frontiers in Plant Science, 2020)
Nitrogen-fixing heterocystous cyanobacteria are used as biofertilizer inoculants for stimulating plant growth but can also alleviate plant stress by exometabolite secretion. However, only a small number of studies have focused on elucidating the identity of said bioactives because of the wide array of exuded compounds. Here, we used the root hair assay (RHA) as a rapid programmed cell death (PCD) screening tool for characterizing the bioactivity of cyanobacteria Nostoc muscorum conditioned medium (CM) on Arabidopsis thaliana root hair stress tolerance. We found that heat-stressed A. thaliana pre-treated with N. muscorum CM fractions exhibited significantly lower root hair PCD levels compared to untreated seedlings. Treatment with CM increased stress tolerance by suppressing PCD in root hairs but not necrosis, indicating the bioactive compound was specifically modulating the PCD pathway and not a general stress response. Based on documented N. muscorum exometabolites, we identified the stress-responsive proline as a compound of interest and strong evidence from the ninhydrin assay and HPLC indicate that proline is present in N. muscorum CM. To establish whether proline was capable of suppressing PCD, we conducted proline supplementation experiments. Our results showed that exogenous proline had a similar effect on root hairs as N. muscorum CM treatment, with comparable PCD suppression levels and insignificant necrosis changes. To verify proline as one of the biologically active compounds in N. muscorum CM, we used three mutant A. thaliana lines with proline transporter mutations (lht1, aap1 and atprot1-1::atprot2-3::atprot3-2). Compared with the wild-type seedlings, PCD-suppression in lht1and aap1 mutants was significantly reduced when supplied with low proline (1–5 μM) levels. Similarly, pre-treatment with N. muscorum CM resulted in elevated PCD levels in all three mutant lines compared to wild-type seedlings. Our results show that plant uptake of cyanobacteria-derived proline alters their root hair PCD sensitivity threshold. This offers evidence of a novel biofertilizer mechanism for reducing stress-induced PCD levels, independent of the existing mechanisms documented in the literature.